Reducing dyspeptic symptoms in children: proton pump inhibitor vs. H2 receptor antagonist - Tien Budi Febriani; Titis Widowati; Mohammad Juffrie (Paediatrica Indonesiana, 2014)
Background Dyspepsia is known as a leading cause of uppergastrointestinal tract morbidity. If left untreated, dyspepsia maybecome chronic. Dyspeptic symptoms manifest as epigastricpain, heartburn, nausea, hematemesis, or melena. Experimentalstudies have shown that omeprazole is more effective at reducingheartburn than ranitidine in adults. However, there have beenfew studies comparing the effects of proton pump inhibitorsto Hz receptor antagonists for reducing dyspeptic symptoms inchildren.Objective To compare the effect of omeprazole with ranitidinefor reducing dyspeptic symptoms .Methods We performed a double-blind randomized controlledtrial (RCT) at Sardjito Hospital and three community h ealthcenters in the Sleman District from June to November 2012.We recruited children aged 3-18 years with dyspepsia. Subjectswere allocated into two groups using block randomization:the proton pump inhibitor (omeprazole) and the Hz receptorantagonist (ranitidine) groups. According to the groups, eitheromeprazole (0.4-0 .8 mg/kg/dose) or ranitidine (2-4 mg/kg/dose) ,respectively, were taken twice daily for 5 days. Dyspepsia wasclinically diagnosed using the new Rome III criteria. Both groupswere monitored for 5 days to assess for a reduction of dyspepticsymptoms.Results Significantly more subjects in the omeprazole grouprecovered from dyspeptic symptoms than in the ranitidine group(RR= 4.87; 95%CI 1.5 to 15.3; P=0.005).Conclusion Omeprazole was 4.87 (95% CI 1.5 to 15.3) timesbetter than ranitidine in reducing dyspeptic symptoms on childrenaged 3-18 years with dyspepsia.